Seasonal variations in ectopic pregnancy rate [Ektopik gebeliklerin tüm konsepsiyonlara oraninin mevsimsel deǧişkenliǧi] - (:unkn) unknown (My University, 2004)
OBJECTIVE: To determine the seasonal variations in ectopic pregnancy rate in our clinic. STUDY DESIGN: All pregnant women who referred to Department of Obstetrics and Gynecology, Marmara University School of Medicine, Istanbul and had their last menstrual periods between January 1993 and January 2003 were included in this study. Subjects were divided into four groups according to the season corresponding to their last menstrual periods, and these groups were compared for ectopic pregnancy rates by using the chi-square test. Seasonal variation in ectopic pregnancy rate was also analyzed in different age groups. The rates in the initial and latter halves of the 10-years-period were also compared. RESULT(s): Of 4,714 pregnancies included, 30 (0.6%) resulted in ectopic pregnancies. The ratio of ectopic pregnancy (EP) to total conceptions (C) was not different between seasons, and also no seasonal difference was noted in different age groups. EP/C ratio significantly increased in conceptions in the latter half of the last 10 years, when compared to the initial 5-years-period. CONCLUSION(s): The present study indicates that ectopic pregnancy rate shows no seasonal variations. However, there was an increase in ectopic pregnancy rate in recent years.
Keywords: Ectopic Pregnancy; Seasonal Variation